Biogeografia de haplogrupos do gênero Metachirus (Didelphidae): Filogenética, distribuição geográfica e sistemática molecular - Bolzan, Angelica Aparecida Simões (2021)
The genus Metachirus, currently composed of two species (M. myosuros and M. nudicaudatus) and with wide distribution throughout South America and part of Central America, stands out among the Didelphidae as one of the groups with priority demands for elucidation of phylogenetic relationships among its components, having been the target of taxonomic, phylogenetic, and morphological studies, but still without current consensus on its systematics. This study used an integrative approach, combining the use of niche modeling, spatial statistics and phylogenetic analyses from secondary data, in order to contribute to the understanding of molecular systematics and distribution of Metachirini tribe groups. As a result, we found seven haplogroups that occur allopátricly, five of which may correspond to taxonomic entities already described and the others to taxonomic entities not yet formally recognized. Analyses of niche overlap, P distance, Fst, molecular dating, ecological analyses and haplotypes indicate the occurrence of an evolutionary process, associated with the large rivers of the Amazon and the Brazilian biomes, having as main hypothesis of maintenance of genetic diversity the existence of biogeographic barriers. A correlation was also observed between areas of Amazonia endemism and the population structure observed in the haplogroups studied. In view of the results achieved, it is proposed the resumption of subspecies for this group, since this classification would more comprehensively represent the genetic diversity of the group and corroborate the conservation of both its components and its areas of occurrence.